2020
DOI: 10.2196/15704
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Usability and Acceptability of Wearable Sensors Among Older Irish Adults in a Real-World Context: Observational Study

Abstract: Background Wearable devices are valuable assessment tools for patient outcomes in contexts such as clinical trials. To be successfully deployed, however, participants must be willing to wear them. Another concern is that usability studies are rarely published, often fail to test devices beyond 24 hours, and need to be repeated frequently to ensure that contemporary devices are assessed. Objective This study aimed to compare multiple wearable sensors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 38 publications
(57 reference statements)
2
63
0
Order By: Relevance
“…Although this method was implemented using professionals/researchers, a similar approach could also be used to evaluate user perspectives. This approach’s novelty allows researchers to assess the relevance of domains that were previously quantified only in isolation [ 33 , 34 , 35 , 36 , 37 , 39 , 40 ], such as the wearability and usability of a device, in combination with aspects related to its validity and other domains. This ensures a more robust choice of a specific solution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this method was implemented using professionals/researchers, a similar approach could also be used to evaluate user perspectives. This approach’s novelty allows researchers to assess the relevance of domains that were previously quantified only in isolation [ 33 , 34 , 35 , 36 , 37 , 39 , 40 ], such as the wearability and usability of a device, in combination with aspects related to its validity and other domains. This ensures a more robust choice of a specific solution.…”
Section: Discussionmentioning
confidence: 99%
“…Widespread deployment of wearables requires “perceived usefulness” by the stakeholders, and benefits of use to be balanced with “perceived ease of use” [ 43 ]. Comfort, battery life, and feedback provided by the device are additional elements to be considered within this domain [ 35 , 36 ], as well as its size, location, and method of attachment to the body [ 39 , 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(56) Keogh et al pointed out that a short battery life has impeded the development of wearable healthcare devices. (66) Puri's group also found that most elderly people would prefer wearable healthcare devices to have a longer battery life. (64) In addition to the above functional requirements, many studies demonstrated the high demand for aesthetic factors, such as colors, shapes, and sizes.…”
Section: Requirements Of Wearable Healthcare Devices For Elderly Peoplementioning
confidence: 99%
“…In other words, it provides an understanding of how much people move or sleep, but not how this is dispersed within days, weeks or months. Recent research suggests that more complex methods of data processing may provide more meaningful clinical insights [11], while users may value further detail than that which is currently provided by many devices [12]. More granular visual representations of data may offer the ability to quickly identify patterns and understand behaviour, therefore informing clinical decision-making and driving increased use of wearables in practice [10, 13].…”
Section: Introductionmentioning
confidence: 99%